Hypertriglyceridemia and Intravenous Lipid Titration During Routine Parenteral Nutrition in Small Preterm Infants. Issue 5 (November 2019) - Correani, Alessio; Giretti, Ilaria; Antognoli, Luca; Monachesi, Chiara; Cogo, Paola; D'Ascenzo, Rita; Biagetti, Chiara; Carnielli, Virgilio P.
ABSTRACT: Objectives: In case of hypertriglyceridemia (HiTG) during parenteral nutrition (PN), the 2018 European Society of Paediatric Gastroenterology, Hepatology and Nutrition guidelines recommend an intravenous (IV) lipid titration, but its consequences in small preterm infants are largely unknown. We compared macronutrient and energy intakes, growth, diseases associated with prematurity, and neurodevelopment in small preterm infants on PN who developed (cases) or did not develop HiTG (controls, CNTR). Methods: We retrospectively reviewed data of preterm infants with a birth weight (BW) <1250 g consecutively admitted to our neonatal intensive care unit (2004–2016) who received routine PN. HiTG infants were defined by at least 1 triglyceride (TG) measurement >250 mg/dL during the first 10 days of life. Patients with and without HiTG were match-paired for BW and gestational age. Results: A total of 658 infants were analyzed and 196 (30%) had HiTG. One hundred thirty-six HiTG patients were matched with 136 CNTR. In the first 10 days of life, IV lipid, non-protein energy and total energy intakes, but not IV amino acids and carbohydrates, were significantly lower in HiTG infants. We found no differences between groups in diseases associated with prematurity. Anthropometry at 36 weeks (W), anthropometry at 2-year (Y) corrected age (CA), and neurodevelopment at 2Y CA were not different. Conclusions: Growth, diseases associated with prematurity, and neurodevelopment at 2Y CA in HiTG infants were similar to CNTR. This occurred despite a statistically significant albeit small reduction in IV lipid and non-protein energy intakes due to a strict TG monitoring and IV lipid titration at TG levels >250 mg/dL.